2006
DOI: 10.1680/geot.2006.56.10.677
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge modelling of wet deep mixing processes in soft clays

Abstract: This paper assesses the feasibility of studying wet deep mixing processes using centrifuge modelling. The scaling relationships relevant to modelling of the deep mixing were first established, and the likelihood of satisfying them in centrifuge modelling was then examined. The relationships between most of the significant forces in deep mixing processes can be satisfied using centrifuge modelling, with the exception of the Reynolds number. The latter cannot be preserved, owing to the non-Newtonian characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Under such conditions, soil viscosity is not correctly scaled (Lee, 2006). However, Ishihara (1996) and Banerjee (2010) noted that rate-dependent viscous damping in the soft clay is much smaller than strain-dependent hysteretic damping.…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, soil viscosity is not correctly scaled (Lee, 2006). However, Ishihara (1996) and Banerjee (2010) noted that rate-dependent viscous damping in the soft clay is much smaller than strain-dependent hysteretic damping.…”
Section: Introductionmentioning
confidence: 99%
“…(3) and (4) can be readily unified as F c ¼ b  q u , of which the coefficient b from both equations were plotted against the COV of UCS as shown in Fig. 13.…”
Section: Engineering Applicationmentioning
confidence: 99%
“…These techniques involve mixing admixtures, usually cementitous, into soft soils by way of hollow rotating shafts with cutting tools, mixing paddles and/or augers mounted at various locations along the shafts (e.g. among others, [1][2][3][4][5]). It is well known that this process of chemical improvement can introduce significant heterogeneity into the improved ground.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar way, significant non-uniformities can result from chemical improvement using cement slurry (e.g. Lee et al 2005Lee et al , 2006Lee et al , 2008. Chen et al (2011) also reported that the unconfined compressive strength (UCS) of core samples varies from about 700 kPa to about 5 MPa for the deep mixing work at the Marina Bay Financial Centre (MBFC) project in Singapore.…”
Section: Introductionmentioning
confidence: 95%